Depressive Symptoms in Women with Gestational Diabetes Mellitus: The LINDA-Brazil Study - Patrícia Damé; Kadhija Cherubini; Pâmella Goveia; Geórgia Pena; Leony Galliano; Cristina Façanha; Maria Angélica Nunes (Journal of Diabetes Research)
This study aimed to assess the frequency and severity of depressive symptoms and their relationship with sociodemographic characteristics in women with gestational diabetes mellitus (GDM) who participated in the LINDA-Brazil study. We conducted cross-sectional analyses of 820 women with GDM who were receiving prenatal care in the public health system. We conducted structured interviews to obtain clinical and sociodemographic information and applied the Edinburgh Postnatal Depression Scale (EPDS) to assess depressive symptoms. We classified the presence and severity of depressive symptoms using scores of ≥12 and ≥18, respectively. We used Poisson regression to estimate prevalence ratios (PR). Most of the women lived with a partner (88%), 50% were between 30 and 39 years old, 39% had finished high school, 39% had a family income of 1-2 minimum wages, and 47% were obese before their pregnancies. The presence of depressive symptoms was observed in 31% of the women, and severe depressive symptoms were observed in 10%; 8.3% reported self-harm intent. Lower parity and higher educational levels were associated with lower EPDS score. Depressive symptoms were common and frequently severe among women with GDM, indicating the need to consider this situation when treating such women, especially those who are more socially vulnerable. This trial is registered with NCT02327286, registered on 23 December 2014.